Validation of DSM-5 age-of-onset criterion of attention deficit/hyperactivity disorder (ADHD) in adults: Comparison of life quality, functional impairment, and family function. (December 2015) - Lin, Yu-Ju; Lo, Kuan-Wu; Yang, Li-Kuang; Gau, Susan Shur-Fen
Highlights: We verify the DSM-5 ADHD criteria by functional impairment and life quality. We compare ADHD adults with onset by and after 7 years old and non-ADHD controls. There is no difference of impairments between the two age-of-onset ADHD groups. Family support and anxiety/depression mediate early/late-onset ADHD to impairments. Abstract: The newly published Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (DSM-5) elevates the threshold of the ADHD age-of-onset criterion from 7 to 12 years. This study evaluated the quality of life and functional impairment of adults with ADHD who had symptoms onset by or after 7 years and examined the mediation effect of family function and anxiety/depression symptoms between ADHD diagnosis and quality of life and functional impairment. We assessed 189 adults with ADHD and 153 non-ADHD controls by psychiatric interview and self-administered reports on the Adult ADHD Quality of Life Scale, Weiss Functional Impairment Rating Scale, Family APGAR, and Adult Self Report Inventory-4. The ADHD group was divided into early-onset ADHD (onset <7 years, n  = 147) and late-onset ADHD (onset between 7 and 12 years, n  = 42). The mediation analysis was conducted to verify the mediating factors from ADHD to functional impairment and quality of life. The late-onset ADHD had more severe functional impairment at work and poorer family support than early-onset ADHD while they had comparable impairment at other domains. Less perceived family support and current anxiety/depressive symptoms partially mediated the link between ADHD diagnosis and quality of life/functional impairment both in early- and late-onset ADHD. Our data support decreased quality of life and increased functional impairment in adult ADHD, regardless of age of onset, and these adverse outcomes may be mediated by family support and anxiety/depression at adulthood. Our findings also imply that the new DSM-5 ADHD criteria do not over-include individuals without impairment.